PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BAGI ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH INKLUSI - Isroani, Farida (Pascasarjana IAIN Kudus, 2019)
This study aims to determine the management of PAI learning in the Inclusion school. In this study the authors analyzed the data with qualitative analysis techniques. The findings in this study are four, among others (1) PAI learning planning for ABK in inclusion settings (2) implementation of PAI learning with various strategies (3) Evaluation of PAI learning outcomes (4) Constraints faced both in planning, implementing and evaluating PAI learning in inclusive schools. Keyword: management, learning PAI, ABK